Analysis of Consumer Satisfaction Levels on the Value of Sagoku Products From Sago Meambo Food, Mata output, Kendari District. - La Ode Muhammad Arif; La Rianda; Sakir Sakir (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2022)
This study aims to study the process of sago processing at the Meambo Food Sago Business in the Mata Village, Kendari District, Kendari City, to determine the product development process using the Quality Function Deployment (QFD) method on sago processing at the Meambo Food Sago Business in the Mata Village, Kendari District, Kendari City. ". Data was collected using questionnaire, interview, documentation and observation methods. The results showed that the process of processing sago products from sago Meambo food The processing of Sagoku Meambo Food products begins with the post-harvest stage of sago fruit carried out by sago farmers who have collaborated with Meambo Food Sago Enterprises, then the next stage is the processing of sago into flour carried out by labor. The sago processing process is by washing sago, soaking sago, roasting sago using an oven, sifting sago using a sieve to produce sago flour, then using sago flour to make sago products. The needs of consumers in a row include: having a halal label (8.93%), including an expiration date (8.87%), including information on the type of taste (8.18%), sweetness (7.93%), new topping/stuffing variants (7.75%) ), more toppings/filling (7.75%), easy to get chocolate products (7.39%), no bitter taste (7.33%), unchanged taste (7.28%), soft texture (7.28%) , Has information on nutritional value in one package (7.28%) and packaging color according to product (6.57%).